Risk factors for diarrheal diseases among pilgrims during Arba’een mass gathering: a case-control study - Hosein Azizi; Elham Davtalab Esmaeili; Behrouz Naghili; Shahriyar Ghanbarzadeh Javid; Ehsan Sarbazi; Fariba Abbasi (BMC Infectious Diseases, 2024)
Abstract Background A significant portion of the Muslim community participates in the Arba’een pilgrimage, with participant numbers increasing each year. There have been relatively few studies on the health of Arba’een Mass gathering (MG). Researching the prevalence and distribution of diseases among Arba’een pilgrims is essential to recognize any outbreaks and take timely responses to contain them. The current study aimed to identify exposures and risk factors for diarrheal disease in pilgrims who referred to the clinics located in Iraq among the Arba’een MG in 2023. Methods This case-control study randomly selected 200 outpatients (100 cases and 100 controls) who were referred to Iraq clinics. Cases were patients with gastrointestinal symptoms (diarrhea), while controls were randomly selected from unaffected pilgrims at the same time for the cases. The study groups matched for age, and sex. Face-to-face interviews using a reliable field based checklist of the Center for Disease Control and Prevention of Iran’s Ministry of Health to collect potential exposures and risk factors for diarrheal disease. Multiple logistic regression was used to estimate the crude and adjusted odds ratio (AOR) for the risk of diarrhea with a 95% confidence interval (CI). Results The average age of the participants was 38.6 years. Diarrhea in 100% and fever in 81% were the most common clinical symptoms in patients. Having underlying diseases was not associated with an increased risk of diarrhea disease (P > 0.05). Regarding risk factors for diarrheal, the final analysis after adjusting for potential confounders indicated that consumption of insanitary (unpackaged) drinking water (AOR = 1.95; 95% CI: 1.05–3.6; P = 0.024), inappropriate hand washing (AOR = 3.82; 95% CI: 1.7–8.6; P = 0.001), ritual foods (AOR = 2.56; 95% CI: 1.3–5.2; P = 0.004), and public toilets (AOR = 1.46; 95% CI: 1.04–4.3; P = 0.038) were significantly increased the likelihood of diarrheal disease. Conclusions Contamination of water sources, food, inadequate and poor hand washing were the most common sources of diarrheal diseases among Arba’een pilgrims. The results indicate that the potential occurrence of outbreaks, especially water- and foodborne diseases, threatens participants in the Arba’een MG. It is recommended to provide risk assessment, improve pilgrims’ awareness, pre-and post-screening, vaccination, compliance with personal hygiene, improvement of the environment, provision of sanitary water and food sources and hygienic disposal of sewage, laboratory diagnosis to identify the common types of pathogens in Arba’een MG.